Digital book of basic conversations to improve the speaking skills in students of tenth grade at Unidad Educativa Prof. Cleofé Apolinario Orrala. Rio Verde, Santa Elena, province of Santa Elena. school year 2017-2018. - Borbor Borbor, Danny Javier (2018)
The principal objective of this project is to build up speaking skills through the implementation of a digital book consisting of basic conversations addressed to students of tenth grade at Unidad Educativa “Prof. Cleofé Apolinario Orrala”. In order to give technical support to the present research project it was necessary to research and develop information throughout the four chapters of the thesis project. The theoretical framework, the research methodology, and the implementation of the proposal, which describes the detailed process during the application of the digital book until the final assessment applied to the students’ performance based on the level of improvement of their speaking skills. The proposal of the implementation of the digital book with basic conversations to improve speaking skills represents the main accomplishment in this project. After the application of the digital book, it was confirmed that students improved their speaking skills, and the students felt more motivated to participate and learn by means of basic and interactive conversations guided by the digital English book.